R&D spillovers and the role of economic freedom - Tee, Chee-Lip; Wan Ngah, Wan Azman Saini; Ibrahim, Saifuzzaman; Ismail, Normaz Wana (Universiti Putra Malaysia, 2015)
This paper examines the role of economic freedom plays in moderating research and development (R&D) spillovers from developed to developing countries. Two channels are analyzed namely import and international student flows. The empirical results based on generalized method-of-moment system estimation on a panel of 75 developing countries show that spillover effects through import and international student flow are significant, but the latter channel appear to be more important in term of magnitude. This finding is consistent with view that technology diffusion via human capital mobility should not be underestimated. More importantly, the finding reveals that countries with higher level of economic freedom benefit more from R&D spillovers. This provides further support to the idea that successful knowledge acquisition requires absorptive capacity.